Fatty Acids in Six Small Pelagic Fish Species and Their Crustacean Prey from the Mindanao Sea, Southern Philippines - Ephrime Bicoy Metillo; Anna Arlene Aspiras-Eya (Tropical Life Sciences Research, 2014)
Fatty acids are important in human health and useful in the analysis of the marine food web, however information on tropical pelagic organisms is scarce. Six zooplanktivorous small pelagic fish species (Decapterus kurroides, Decapterus macarellus, Selar crumenophthalmus, Sardinella lemuru, Spratilloides gracilis and Stolephorus insularis) and four of their zooplanktonic crustacean prey [three sergestoid species (Acetes erythraeus, Acetes intermedius and Lucifer penicillifer) and one calanoid copepod (Acartia erythraea)] were collected from the Mindanao Sea, and their fatty acids were profiled. The resulting profiles revealed 17 fatty acids that were specific to certain species and 9 myristic acid [C14:0], palmitic acid [C16:0], stearic acid [C18:0]; palmitoleic acid [C16:1], oleic acid [C18:1n9c], linoleic acid [C18:2n6c], linolenic acid [C18:3n3], eicosapentaenoic acid (EPA) [C20:5n3] and docosahexaenoic acid (DHA) [C22:6n3] that were common to all species. Cluster analysis and non-metric multidimensional scaling (NMDS) of fatty acids indicate a high similarity in profiles in all species, but separate fish and zooplankton clusters were obtained. Mackerel species (D. macarellus, D. kurroides and S. crumenophthalmus) had concentrations of total n-3 fatty acids that match those of their Acetes prey. The copepod A. erythraea and the sergestoid L. penicillifer exhibited the lowest values of the EPA:DHA ratio, which was most likely due to their phytoplanktivorous feeding habits, but the occurrence of the highest values of the ratio in Acetes suggests the inclusion of plant detritus in their diet. DHA values appear to affirm the trophic link among copepod, Lucifer, Acetes and mackerel species. Asid lemak adalah penting untuk kesihatan manusia dan berguna dalam analisis jaringan makanan marin, namun demikian maklumat tentang organisma pelagik tropikal adalah kurang. Enam spesies ikan pelagik kecil zooplanktivorous (Decapterus kurroides, Decapterus macarellus, Selar crumenophthalmus, Sardinella lemuru, Spratilloides gracilis dan Stolephorus insularis) dan empat mangsa krustasia zooplanktonik ikan tersebut [tiga spesies sergestoid (Acetes erythraeus, Acetes intermedius dan Lucifer penicillifer) dan satu spesies kopepoda kalonoid (Acartia erythraea)] telah dikumpul dari Laut Mindanao, dan kandungan asid lemak haiwan-haiwan tersebut telah diprofil. Profil-profil yang terhasil menunjukkan 17 asid lemak yang spesifik kepada spesies tertentu dan 9 asid miristik [C14:0], asid palmitik [C16:0], asid stearik [C18:0]; asid palmitoleik [C16:1], asid oleik [C18:1n9c], asid linoleik [C18:2n6c], asid linolenik [C18:3n3], asid eikosapentaenoik (EPA) [C20:5n3] dan asid dokosaheksaenoik (DHA) [C22:6n3] yang am bagi semua spesies. Analisis kluster dan penskalaan multidimensi bukan-metrik (NMDS) asid lemak telah menunjukkan persamaan yang tinggi dalam profil semua spesies, tetapi kluster yang berasingan telah diperoleh untuk ikan dan zooplankton. Jumlah kandungan n-3 asid lemak spesies makerel (D. macarellus, D. kurroides dan S. crumenophthalmus) menyamai pemangsa Acetes. Kopepoda A. erythraea dan sergestoid L. penicillifer telah menunjukkan nilai nisbah EPA:DHA yang paling rendah, yang besar kemungkinan akibat tabiat pemakanan phytoplanktivorous mereka, namun demikian nilai tertinggi nisbah tersebut dalam Acetes mencadangkan kemasukan detritus tumbuhan dalam diet mereka. Nilai DHA seakan mengesahkan pautan trofik antara kopepoda, Acetes dan spesies makerel.